The mediating role of biological age in the association between dietary index for gut microbiota and sarcopenia - Zhang, Jingyuan; Guo, Jun; Zhang, Jing; Liu, Heng; Zhou, Lin; Cheng, Chi; Cao, Hong (Frontiers in Immunology, 2025)
BackgroundDietary Index of Gut Microbiota (DI-GM) is a newly proposed comprehensive metric for assessing dietary quality in relation to gut microbiota composition. Alterations in muscle structure are closely linked to DNA methylation-based biological age assessments and individual dietary patterns. However, a systematic investigation of the interrelationships among DI-GM, biological age, and sarcopenia remains lacking. We hypothesize that consuming foods beneficial to the gut microbiota may help mitigate the risk of sarcopenia by slowing the aging process.MethodsThis study analyzed data from NHANES 2007–2018. DI-GM was calculated using two 24-hour dietary recall datasets. Sarcopenia was assessed via dual-energy X-ray absorptiometry (DXA). The association between DI-GM and sarcopenia was evaluated using multivariate logistic regression, subgroup analysis, and restricted cubic splines. This study also investigated the potential mediating effects of three biological age indicators: the Klemera-Doubal Method (KDM), PhenoAge, and Homeostatic Dysregulation (HD).ResultsAn increase in DI-GM score was significantly associated with a reduced risk of sarcopenia (OR: 0.87, 95% CI: 0.82–0.94).The risk of sarcopenia was significantly lower in the highest quartile group (Q3) (OR: 0.25, 95% CI: 0.11–0.58). The three biological age-related indicators (KDM, PA, and HD) partially mediated the association between DI-GM and sarcopenia, with PhenoAge showing the highest mediation proportion at 30.6%.ConclusionA higher DI-GM score was significantly associated with a reduced risk of sarcopenia. PhenoAge, HD, and KDM demonstrated significant mediating effects, with PhenoAge showing the highest mediation proportion.